Medulloblastoma - Indu Rekha Meesa (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2019)
Pediatric brain tumors are the most common solid tumors that develop in children second only to leukemia. They also account for the most cancer deaths in this patient population [1]. 7% of all the brain tumors that were diagnosed between 2006 and 2010 in the United States were in patients younger than 20 years of age [2]. Infratentorial tumors account for 45%-60% of brain tumors in children [3]. Some of the most common pediatric posterior fossa tumors are medulloblastoma, ependymoma, pilocytic astrocytoma, and atypical teratoid rhabdoid tumors. Medulloblastoma will be discussed in this paper.